2007
DOI: 10.1590/s0101-31572007000300004
|View full text |Cite
|
Sign up to set email alerts
|

A new cultural cleavage in post-modern society

Abstract: The attitudes towards gender and homosexuality tend to be linked at the micro level (individuals), which explains the political saliency of this newly emerging cleavage. At the macro level (country), the main finding is that the value orientations towards gender and homosexuality are strongly embedded in the basic cultural or civilisation differences among countries. As developing countries modernise and enter post-modernity, they will also experience the gender cleavage, especially when they adhere to an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Moreover, RF also has a better out-of-box performance. As Probst et al [20] have shown, random forests have the least variability in their prediction accuracy when tuning among popular machine learning algorithms. To further show the performance of classification models, the ROC curves of RF with different split strategies and different algorithms are drawn in Fig.…”
Section: Robustness Checkmentioning
confidence: 99%
“…Moreover, RF also has a better out-of-box performance. As Probst et al [20] have shown, random forests have the least variability in their prediction accuracy when tuning among popular machine learning algorithms. To further show the performance of classification models, the ROC curves of RF with different split strategies and different algorithms are drawn in Fig.…”
Section: Robustness Checkmentioning
confidence: 99%
“…When we turn to the plot on the right, which attempts to more closely examine the link between sexual and gender equality (Frank and McEneaney, 1999; Lane, 2007) by substituting women’s parliamentary representation on the x-axis, 3 the perspective changes and the overall strength of the relationship is cut in half. This is due, in part, to a cleavage between the two sub-regions—classified by Welzel (2013) as “Sinic” and “Indic” and shaded accordingly.…”
Section: The Condition Of Sexuality and Gender Politics In Southeast mentioning
confidence: 99%